Early changes of peripheral circulating immune subsets induced by PD-1 inhibitors in patients with advanced malignant melanoma and non-small cell lung cancer - Simona Borilova; Peter Grell; Iveta Selingerova; Lenka Gescheidtova; Marie Mlnarikova; Ondrej Bilek; Radek Lakomy; Alexandr Poprach; Jan Podhorec; Igor Kiss; Rostislav Vyzula; Barbora Vavrusakova; et al. (BMC Cancer)
Abstract Background Immune checkpoint inhibitors (ICIs), including those targeting PD-1, are currently used in a wide range of tumors, but only 20–40% of patients achieve clinical benefit. The objective of our study was to find predictive peripheral blood-based biomarkers for ICI treatment. Methods In 41 patients with advanced malignant melanoma (MM) and NSCLC treated with PD-1 inhibitors, we analyzed peripheral blood-based immune subsets by flow cytometry before treatment initialization and the second therapy dose. Specifically, we assessed basic blood differential count, overall T cells and their subgroups, B cells, and myeloid-derived suppressor cells (MDSC). In detail, CD4 + and CD8 + T cells were assessed according to their subtypes, such as central memory T cells (TCM), effector memory T cells (TEM), and naïve T cells (TN). Furthermore, we also evaluated the predictive value of CD28 and ICOS/CD278 co-expression on T cells. Results Patients who achieved disease control on ICIs had a significantly lower baseline proportion of CD4 + TEM (p = 0.013) and tended to have a higher baseline proportion of CD4 + TCM (p = 0.059). ICI therapy-induced increase in Treg count (p = 0.012) and the proportion of CD4 + TN (p = 0.008) and CD28 + ICOS- T cells (p = 0.012) was associated with disease control. Patients with a high baseline proportion of CD4 + TCM and a low baseline proportion of CD4 + TEM showed significantly longer PFS (p = 0.011, HR 2.6 and p ˂ 0.001, HR 0.23, respectively) and longer OS (p = 0.002, HR 3.75 and p ˂ 0.001, HR 0.15, respectively). Before the second dose, the high proportion of CD28 + ICOS- T cells after ICI therapy initiation was significantly associated with prolonged PFS (p = 0.017, HR 2.51) and OS (p = 0.030, HR 2.69). Also, a high Treg count after 2 weeks of ICI treatment was associated with significantly prolonged PFS (p = 0.016, HR 2.33). Conclusion In summary, our findings suggest that CD4 + TEM and TCM baselines and an early increase in the Treg count induced by PD-1 inhibitors and the proportion of CD28 + ICOS- T cells may be useful in predicting the response in NSCLC and MM patients.